221 UK Medical School Selection Criteria Predicts Success in Part A of The Intercollegiate Membership of The Royal College of Surgeons (MRCS) Examination. (4th May 2021) - Ellis, R; Brennan, P; Cleland, J; A. Lee,; D. Scrimgeour,
Abstract: Background: Selection into UK medical school typically involves a combination of three measures: prior academic attainment, selection tests (e.g., the University Clinical Aptitude Test (UCAT), Biomedical Admissions Test (BMAT), Graduate Medical School Admissions Test (GAMSAT)), and an interview. We investigated whether prior attainment and selection test scores can predict MRCS success. Method: We used the UKMED database to analyse selection data for all UK graduates who attempted MRCS Part A (n = 9729) and Part B (n = 4644) between 2007-2017. Univariate analysis and Pearson correlation coefficients were used to examine the relationship between selection scores and first attempt MRCS success. Results: Successful MRCS Part A candidates had better A-Levels and higher scores in UCAT, BMAT and GAMSAT examinations (p < 0.001) than their unsuccessful peers. No statistically significant difference was observed for MRCS Part B. A moderate positive correlation was found between Part A, BMAT (r = 0.315, p < 0.001) and GAMSAT scores (r = 0.346, p < 0.001). A weak positive correlation was found between Part A, A-Level (r = 0.144, p < 0.001) and UCAT scores (r = 0.246, p < 0.001). Conclusions: A-level results and medical school selection tests predict success in the knowledge-based (Part A) MRCS examination.